Pengembangan Video Pembelajaran Berbasis Powtoon Materi Kimia Unsur untuk SMA/MA Kelas XII - Nisa, Syarafina Ainun (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
Teachers often face challenges in implementing new teaching methods in order to arouse students' learning motivation. The use of technology has the potential to improve the quality of education in schools, efficiency and effectiveness in the teaching and learning process, and act as a tool to enrich knowledge and sources of information for learning. The aim of this research is to create learning video material using the Powtoon platform for the topic of elemental chemistry, as well as evaluating the quality of the learning video as a learning tool on this topic. The evaluation was carried out by experts in the field of chemical materials, experts in the field of media, chemistry teachers, and responses from students. This study adopts a research and development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model, but the focus is only limited to the Implementation stage. The result is a learning video that is available in .mp4 format and can be viewed on YouTube. This video covers material about chemical elements. According to the assessment of material experts, the product received a score of 95% in the very good (VG) category; assessment from media experts shows a score of 94.29% also in the very good category (VG); while the assessment from high school chemistry teachers resulted in a score of 83.64% in the very good category (VG). This product received a positive response from all class XII high school students, reaching a satisfaction level of 100%. According to the evaluation that has been carried out, learning videos can be an effective teaching option for teaching elemental chemistry material in the classroom.